The deconstruction of the welfare State: changes in the practice of social workers and increase in social volunteers - Barrera Algarín, Evaristo; Malagón Bernal, José Luis; Sarasola Sánchez-Serrano, José Luis (Cuadernos de Trabajo Social, 2013)
The article is based on a historical connection between the welfare states formation, the parallel development of social work, and the social volunteering evolution in Spain. Based on this relationship, when the welfare states start a deconstruction’s process as we can see, the social work suffers a major adaptation in form and practice. Based on evidences from recent research about social workers in the South of Spain (Andalusia), obtained data as social work modifies paradigmatic and methodological forms, and of course their working conditions and hiring. This research was supported by a quantitative-qualitative methodology, based on a sample of 156 social workers in the Seville’s Province, and was crossed with data from focus groups in a triangulation technique.
Keywords: Social Work; welfare State; paradigm; methodology; research; volunteerism; privatization.